A case of multiple cranial nerve palsies. Issue 6 (5th July 2021) - Gomathy, Saranya; Elavarasi, Arunmozhimaran; Komakula, Snigdha; Modi, Manish; Sharma, MC; Kaur, Kavneet; Garg, Ajay; Tripathi, Madhavi; Kanodia, Anupam; Verma, Hitesh; Vibha, Deepti; Singh, Rajesh K; et al.
Abstract : Multiple cranial nerve palsies have many possible causes, including infective, inflammatory, neoplastic and infiltrative diseases of the meninges or skull base. We present the clinicopathological conference of a 27-year-old man with a smouldering course of sequential cranial nerve palsies. His imaging showed dural thickening and osteosclerosis of the skull base with otomastoiditis. Cerebrospinal fluid showed lymphocytic pleocytosis with reduced glucose and normal protein concentrations. There was a possible response to corticosteroids and anti-tubercular treatment. Initial biopsy from the thickened and enhancing dura was unremarkable. His condition deteriorated after the steroids were tapered; MR imaging showed progression of lesions and positron emission tomography showed intense hypermetabolism. Subsequently, a diagnostic test revealed the final diagnosis. This case was presented at the All India Institute of Medical Sciences' monthly clinicopathological conference series in February 2021.